Harvest load transfer sites influence sugarcane billbug (Coleoptera: Curculionidae) spatiotemporal injury in sugarcane - Rosa, Jivago Oliveira [UNESP]; Soares, João Rafael Silva [UNESP]; Fernandes, Odair Aparecido [UNESP] (Wiley, 2024)
BACKGROUND: The sugarcane billbug, Sphenophorus levis Vaurie 1978, is a key soil-dwelling insect pest of sugarcane in Brazil and greatly affects plant development and yield. This insect presents an aggregated distribution pattern in production fields. The reasons for such behavior include intraspecific communication and attractivity due to the fermentation of sugar in stalk residues. During mechanized harvesting, part of the harvested material usually falls in the load transfer sites, becoming a potential source for increasing the infestation. We therefore evaluated whether producing areas near the harvest load transfer sites are more prone to S. levis injury. RESULTS: There are greater chances of finding billbug injury within a radius of 740 m from the harvest load transfer site. Additionally, injured areas are estimated to expand 11.96% each growing season. Our spatiotemporal models support higher injured areas surrounding the harvest load transfer site and show clear and significant signs of increased injury levels compared to the initial growing season surveyed. CONCLUSION: Our results reinforce the importance of harvest transfer sites in the dispersion and propagation of the sugarcane billbug. Based on this knowledge, sugarcane millers and growers can adopt preventive and remedial practices within the loading sites that can potentially contribute to the successful management of this insect pest. © 2023 Society of Chemical Industry.
Keywords: behavioral ecology; crop residue; cultural practices; geostatistics; species distribution